Management perspective for mantle cell lymphoma. (February 2014) - Shah, Nimish; Rule, Simon
SUMMARY Mantle cell lymphoma (MCL) is genetically characterized by the t(11;14) (q13;q32) translocation resulting in the overexpression of cyclin D1. It generally has an aggressive clinical course with a poor prognosis. However, there is now a recognized subgroup with clinically indolent MCL. Management of MCL can be challenging. Early recognition of young and fit patients for potential intensive therapy and autologous stem cell transplant is important. Combination of rituximab with high-dose cytarabine should be used in upfront therapy for appropriate patients. In elderly and/or less fit patients, chemoimmunotherapy may be considered. Novel agents offer promising potential in the management of MCL and are likely to change the way it is treated.